Investigate of Mechanical Fuse in Cardan Shaft Using FEM - Rabiei, Sayed Poorya; Azarafza, Reza (Review of Information Engineering and Applications, 2014)
A Cardan shaft is a mechanical component for transmitting torque and rotation, usually used to connect drive shaft to driven shaft that cannot be connected directly because of distance or the need to allow for relative movement between them. If overload is applied to cardan shaft, failure can occur in each part of the cardan shaft and maybe some irreparable damage occur to the cardan shaft. Thus it is important to investigate the existence of mechanical fuse in cardan shaft, and this subjcet is analyzed by Abaqus software and the results are illustrated that the cross shaft of an standard cardan shaft, fails first and is the best part as a mechanical fuse.